2020
DOI: 10.1002/pa.2166
|View full text |Cite
|
Sign up to set email alerts
|

Impact of corporate governance mechanisms on the cost of equity capital in emerging markets

Abstract: The purpose of this study is to analyze the effects of corporate governance mechanisms on the cost of equity (COE) of Iranian and Iraqi nonfinancial companies listed in the Iran‐Iraq Stock Exchange. In order to achieve the purpose of the study all listed companies on the Iran‐Iraq Stock Exchange, was considered as population of the study during the period of 2012–2017 (137 Iranian listed companies and 34 Iraqi listed companies). In order to test the relationship between variables, the researchers used a set of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 28 publications
0
29
0
Order By: Relevance
“…This model has already been implemented in Reverte (2012) In order to test the relation between CoE and the control and sustainable variables, we implement a fixed-effect panel data model according to the Hausman test, which analyzes the relation or absence of correlation between the independent variables with the error term (Hausman, 1978). In our study, the p-value of the Hausman test is lower than the 0.05 probability benchmark (0.0262), and therefore, we implement a fixed-effects model as in Faysal et al (2020) and Raimo et al (2020). Also, we lag the environmental score similar to Elsayed and Paton (2005), Horv athov a (2012) and El Ghoul et al (2018).…”
Section: Methodsmentioning
confidence: 99%
“…This model has already been implemented in Reverte (2012) In order to test the relation between CoE and the control and sustainable variables, we implement a fixed-effect panel data model according to the Hausman test, which analyzes the relation or absence of correlation between the independent variables with the error term (Hausman, 1978). In our study, the p-value of the Hausman test is lower than the 0.05 probability benchmark (0.0262), and therefore, we implement a fixed-effects model as in Faysal et al (2020) and Raimo et al (2020). Also, we lag the environmental score similar to Elsayed and Paton (2005), Horv athov a (2012) and El Ghoul et al (2018).…”
Section: Methodsmentioning
confidence: 99%
“…Salehi et al (2020) found that the quality of corporate governance can lower the rate of capital cost in a sample of 975 observations during the period 2012 to 2018. Faysal et al (2021) also, documented a positive relationship board size and chief executive officer (CEO) tenure in reducing the CEO, and a positive role in audit quality in reducing the CEO in the Iranian context. Also, Faysal et al (2021) found a substantial positive related between institutional ownership and the cost of equity in the Iranian and Iraqi.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Faysal et al (2021) also, documented a positive relationship board size and chief executive officer (CEO) tenure in reducing the CEO, and a positive role in audit quality in reducing the CEO in the Iranian context. Also, Faysal et al (2021) found a substantial positive related between institutional ownership and the cost of equity in the Iranian and Iraqi. Thompson and Manu (2021) stated that the corporate governance characteristics (i.e.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Moreover, information asymmetry in banking in emerging markets has been discussed in the recent literature (Tsindeliani and Mikheeva 2021 ; Ghorbani and Salehi 2020 ; Faysal et al. 2021 ).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%